Low dissipative filtration for difference methods of computational fluid dynamics - Sipatov, Aleksey Matveevich; Gomzikov, Leonid Yurievich; Usanin, Mikhail Vladimirovich (Computational Continuum Mechanics, 2011)
Comparison of different filtering methods (explicit Dispersion-Relation-Preserving (DRP) filtering, Shock-Capturing (SC) filtering, wavelet filtration, compact filter with adjustable bandwidth) is presented. It is shown that though 11-points DRP filtering is one of the simplest and fastest methods, its dissipative properties are more pronounced than the properties of Daubechies 6-coefficient wavelet filter and tridiagonal compact 5-point filtering scheme. For the problem under consideration, wavelet-filters appear to be least dissipative. Among the filters producing the lowest level of spurious oscillations in the solution in the neighborhood of shock and apart from the low order filters and high order shock-capturing schemes, a compact filter with adjustable bandwidth is found to be effective